139 Centre of hereditary breast and ovarian cancer at charité – who presents for counseling and why?. (4th December 2020) - Helms, Malina; Kalmbach, Nanette; Neeb, Caroline; Kussmaul, Julia; Speiser, Dorothee
Abstract : Introduction/Background: Since the discovery of the BRCA-genes the knowledge about genetic risk factors for breast and ovarian cancer has multiplied. About 5–10% of all breast cancers and 15–20% of all ovarian cancers are caused by pathogenic mutations in different risk genes. Therefore, the Centre of Hereditary Breast and Ovarian Cancer at Charité offers as one of 20 centres in Germany genetic counseling. The extensive data of the counselees was now evaluated for the first time. The aim of this study was to ease the preparation for counseling sessions and gather information for more individualized counseling. Methodology: Data from 2531 counselees at the Charité-Centre from 2016 and 2017 were evaluated retrospectively. Special emphasis was laid on sociodemographic data and the results of genetic testing. Finally, the mutation frequencies were analyzed in different subgroups. Results: The 2531 counselees were almost exclusively female (n = 2493; 98.5%), 42.9 years old on average and came to the centre for the first time (n = 2198; 86.8%). 2287 (90.4%) counselees met the inclusion criteria for genetic testing. Of these, 863 (37.7%) were already diagnosed with breast or ovarian cancer. 1367 (59.8%) were genetically tested, 918 (67, 2%) as index patients and 449 (32, 8%) predictively. Mutations were detected in 545 (39.9%) tested persons. Most mutations were detected in BRCA1, BRCA2, CHEK2 and ATM. The highest mutation frequency was found among persons from families with both breast and ovarian cancer and in patients with TNBC. A significant correlation was found between mutation frequency in TNBC and age at first diagnosis (figure 1 ). Conclusion: In summary, the collective of counselees at the Charité- Center was described for the first time. The results provide doctors with a comprehensive overview of the counselees, enabling by that an even more individualized counseling and more focused preparation for the consultation. The findings contribute to maintaining the high quality of the genetic counseling at the Centre for Familial Breast and Ovarian Cancer at the Charité (table 1 ). Disclosures: No conflict of interest.